PENERAPAN ASAS LEX SPECIALIS DEROGAT LEGI GENERALIS TERHADAP UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM TINDAK PIDANA PERJUDIAN TOGEL SECARA ONLINE STUDI KASUS PUTUSAN PENGADILAN NEGERI JAKARTA UTARA NOMOR 599/PID.B/2018/PN.JKT UTR - Franky Satrio Darmawan; Dian Andriawan Daeng Tawang (Fakultas Hukum Universitas Tarumanagara, 2018)
Gambling is a crime and can be punished for its actions. However, along with the development of the gambling era it was played with electronic media, namely online gambling. The State of the Republic of Indonesia has overcome gambling crimes with evidence such as the existence of laws contained in criminal law and if carried out online there is an Electronic Information and Transaction law. The research entitled The implementation of principle lex specialis derogat legi generalist concerning information and electronic transaction laws in online lottery gambling crimes Case Study Decision of North Jakarta Districts Courted Number 599 / PID.B / 2018 / PN.Jkt Utr, having a problem statement is why the public prosecutor did not apply the principle of lex specialis derogat legi generalist in the online lottery gambling crime Case Study of the Decision of the North Jakarta District Court Number 599 / PID.B / 2018 / PN.Jkt Utr. The purposed paper for the law enforcement officials to appllied the principled of Lex Specialise Derogat Legi Generalits in the case of prosecution of court decisions.